The Pelagic Laser Tomographer for the Study of Suspended Particulates - M. Dale Stokes; David R. Nadeau; James J. Leichter (Journal of Marine Science and Engineering, 2026)
An ongoing challenge in pelagic oceanography and limnology is to quantify and understand the distribution of suspended particles and particle aggregates with sufficient temporal and spatial fidelity to understand their dynamics. These particles include biotic (mesoplankton, organic fragments, fecal pellets, etc.) and abiotic (dusts, precipitates, sediments and flocks, anthropogenic materials, etc.) matter and their aggregates (i.e., marine snow), which form a large part of the total particulate matter > 200 μm in size in the ocean. The transport of organic material from surface waters to the deep-sea floor is of particular interest, as it is recognized as a key factor controlling the global carbon cycle and hence, a critical process influencing the sequestration of carbon dioxide from the atmosphere. Here we describe the development of an oceanographic instrument, the Pelagic Laser Tomographer (PLT), that uses high-resolution optical technology, coupled with post-processing analysis, to scan the 3D content of the water column to detect and quantify 3D distributions of small particles. Existing optical instruments typically trade sampling volume for spatial resolution or require large, complex platforms. The PLT addresses this gap by combining high-resolution laser-sheet imaging with large effective sampling volumes in a compact, deployable system. The PLT can generate spatial distributions of small particles (~100 µm and larger) across large water volumes (order 100–1000 m3) during a typical deployment, and allow measurements of particle patchiness over spatial scales to less than 1 mm. The instrument’s small size (6 kg), high resolution (~100 µm in each 3000 cm2 tomographic image slice), and analysis software provide a tool for pelagic studies that have typically been limited by high cost, data storage, resolution, and mechanical constraints, all usually necessitating bulky instrumentation and infrequent deployment, typically requiring a large research vessel.

Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

In Silico, Patient-Specific Assessment of Local Hemodynamic Predictors and Neointimal Hyperplasia Localisation in an Arteriovenous Graft - Federica Ninno; Catriona Stokes; Edouard Aboian; Alan Dardik; David Strosberg; Stavroula Balabani; Vanessa Díaz-Zuccarini (Annals of Biomedical Engineering, 2025)
Purpose Most computational fluid dynamics (CFD) studies on arteriovenous grafts (AVGs) adopt idealised geometries and simplified boundary conditions (BCs), potentially resulting in misleading conclusions when attempting to predict neointimal hyperplasia (NIH) development. Moreover, they often analyse a limited range of hemodynamic indices, lack verification, and fail to link the graft-altered hemodynamics with follow-up data. This study develops a novel patient-specific CFD workflow for AVGs using pathophysiological BCs. It verifies the CFD results with patient medical data and assesses the co-localisation between CFD results and NIH regions at follow-up. Methods Contrast-enhanced computed tomography angiography images were used to segment the patient’s AVG geometry. A uniform Doppler ultrasound (DUS)-derived velocity profile was imposed at the inlet, and three-element Windkessel models were applied at the arterial outlets of the domain. Transient, rigid-wall simulations were performed using the k–ω SST turbulence model. The CFD-derived flow waveform was compared with the patient’s DUS image to ensure verification. Turbulent kinetic energy (TKE), helicity and near-wall hemodynamic descriptors were calculated and linked with regions presenting NIH from a 4-month follow-up fistulogram. Results In the analysed patient, areas presenting high TKE and balanced helical flow structures at baseline exhibit NIH growth at follow-up. Transverse wall shear stress index is a stronger predictor of NIH than other commonly analysed near-wall hemodynamic indices, since luminal areas subjected to high values greatly co-localise with observed areas of remodelling. Conclusion This patient-specific computational workflow for AVGs could be applied to a larger cohort to unravel the link between altered hemodynamics and NIH progression in vascular access.

Correction: Optimising Instrumented Mouthguard Data Analysis: Video Synchronisation Using a Cross-correlation Approach - James Tooby; Steve Rowson; Kevin Till; David Allan; Melanie Dawn Bussey; Dario Cazzola; Éanna Falvey; Kenzie Friesen; Andrew J. Gardner; Cameron Owen; Gregory Roe; Thomas Sawczuk; et al. (Annals of Biomedical Engineering, 2025)

Optimising Instrumented Mouthguard Data Analysis: Video Synchronisation Using a Cross-correlation Approach - James Tooby; Steve Rowson; Kevin Till; David Allan; Melanie Dawn Bussey; Dario Cazzola; Éanna Falvey; Kenzie Friesen; Andrew J. Gardner; Cameron Owen; Gregory Roe; Thomas Sawczuk; et al. (Annals of Biomedical Engineering, 2025)
Purpose Head acceleration events (HAEs) are a growing concern in contact sports, prompting two rugby governing bodies to mandate instrumented mouthguards (iMGs). This has resulted in an influx of data imposing financial and time constraints. This study presents two computational methods that leverage a dataset of video-coded match events: cross-correlation synchronisation aligns iMG data to a video recording, by providing playback timestamps for each HAE, enabling analysts to locate them in video footage; and post-synchronisation event matching identifies the coded match event (e.g. tackles and ball carries) from a video analysis dataset for each HAE, this process is important for calculating the probability of match events resulting in HAEs. Given the professional context of iMGs in rugby, utilising commercial sources of coded match event datasets may expedite iMG analysis. Methods Accuracy and validity of the methods were assessed via video verification during 60 rugby matches. The accuracy of cross-correlation synchronisation was determined by calculating synchronisation error, whilst the validity of post-synchronisation event matching was evaluated using diagnostic accuracy measures (e.g. positive predictive value [PPV] and sensitivity). Results Cross-correlation synchronisation yielded mean synchronisation errors of 0.61–0.71 s, with all matches synchronised within 3 s’ error. Post-synchronisation event matching achieved PPVs of 0.90–0.95 and sensitivity of 0.99–1.00 for identifying correct match events for SAEs. Conclusion Both methods achieved high accuracy and validity with the data sources used in this study. Implementation depends on the availability of a dataset of video-coded match events; however, integrating commercially available video-coded datasets offers the potential to expedite iMG analysis, improve feedback timeliness, and augment research analysis.

Evolution of fluvial systems in Eurasia at different time scales - David Bridgland; Tobias Lauer; Martin Stokes (Geomorphology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A brief history of primate research in the Ndoki forest - David Morgan; Richard Malonga; Marcellin Agnagna; Jean Robert Onononga; Valentin Yako; Jerome Mokoko Ikonga; Emma J. Stokes; Crepin Eyana Ayina; Jake A. Funkhouser; Kathryn Judson; Jakob Villioth; Tomoaki Nishihara; et al. (Primates, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Suspended particulates at the Point Loma, California wastewater outfall - M. Dale Stokes; James J. Leichter; David Nadeau (Frontiers in Marine Science, 2023)
A recent study conducted at the Point Loma wastewater outfall in San Diego used a novel sampling technique, the Pelagic Laser Tomographer (PLT), in combination with traditional water column profiling instruments to analyze suspended particulate distributions and effluent plume dynamics. Coastal wastewater discharges create buoyant plumes that interact with the surrounding water, and the tracking and mapping of the resulting diluted effluent is essential for monitoring outfall system performance. The results from the PLT sampling highlight the utility of high spatial and temporal resolution estimates of suspended particulate size spectra to help capture the dynamics of the plume interactions with the coastal current flow field. In addition, new tools like the PLT can help marine scientists estimate natural and anthropogenic particulate size distributions that are essential to our understanding sediment and pollutant transport, nutrient cycling, and ecosystem energy dynamics.

Characteristics and formation of bedrock mega-grooves (BMGs) in glaciated terrain: 2 – conceptual models of BMG initiation - David J.A. Evans; Mihaela Newton; David H. Roberts; Chris R. Stokes (Geomorphology, 2023)

Characteristics and formation of bedrock mega-grooves (BMGs) in glaciated terrain: 1 - morphometric analyses - Mihaela Newton; Chris R. Stokes; David H. Roberts; David J.A. Evans (Geomorphology, 2023)

Method evaluation and risk assessment: A framework for evaluating management strategies for data‐limited fisheries - Thomas R. Carruthers; Quang C. Huynh; Adrian R. Hordyk; David Newman; Anthony D. M. Smith; Keith J. Sainsbury; Kevin Stokes; Alexander Morison; David Agnew; Ana Parma; Ignacio Sobrino; Catherine Longo (Fish and Fisheries, 2023)
Fisheries managers are in need of quantitative tools to inform decisions regarding selection of robust management practices, prioritising research gaps and stocks to focus on, particularly where there are limited resources or data. To support these decisions, the use of Management Strategy Evaluation (MSE), that is, closed loop simulation‐testing of management procedures, is widely regarded as best practice. However, applying MSE is time‐ and computationally intensive, and requires highly skilled expertise and processes for stakeholder input and peer review. For data‐ and capacity‐limited fisheries, MSE may be particularly challenging to implement. Yet, these are the contexts where it is most critical to test assumptions, evaluate the implications of all sources of uncertainty and identify the most informative data sources. To facilitate wider use of MSE, the Method Evaluation and Risk Assessment (MERA) framework was developed as an accessible online interface, with quick processing time, focused on generic data‐limited management procedures, but allowing progression to tailored and more data‐rich methods. The framework links a quantitative questionnaire and data input standard to a flexible operating model with optional customisation via command line access to the back‐end open‐source R libraries. Here, we illustrate a case study application of MERA for the bocinegro ( Pagrus pagrus , Sparidae) fishery in the Gulf of Cadiz, where in conjunction with fishery stakeholders, a custom management procedure was developed and tested and key research gaps and data collection priorities were identified. We discuss implications for wider use of MSE in various contexts, including eco‐certification and fishery improvement projects.

Borderless conservation: Integrating connectivity into high seas conservation efforts for the Salas y Gómez and Nazca ridges - Ben Boteler; Daniel Wagner; Carole Durussel; Emily Stokes; Carlos F. Gaymer; Alan M. Friedlander; Daniel C. Dunn; Felipe Paredes Vargas; David Veliz; Carolina Hazin (Frontiers in Marine Science, 2022)
Connectivity is essential to consider in area-based marine conservation measures because it greatly impacts vital ecological processes (e.g., recycling nutrients, regulating temperature, sequestering carbon, and supporting the life cycle of species). However, it is generally not well studied or integrated into conservation measures, particularly in the Southeast Pacific. This region is home to the Salas y Gómez and Nazca ridges, two adjacent seamount chains that stretch between the Peruvian coast and Rapa Nui (i.e., Easter Island). The area has been recognized for its exceptional natural and cultural significance as well as one of the most important global areas to protect. However, over 73% of the ridges are in areas beyond national jurisdiction, where they are unprotected and under threat. This study provides a synthesis of what we know about connectivity in the Salas y Gómez and Nazca ridges and provides practical recommendations for integrating this knowledge into conservation and management measures for the region. While data on connectivity is still limited, it should not constrain the development of conservation measures, which should be co-designed and co-developed, leveraging the expertise of international working groups throughout the region. Due to their high rates of endemism, as well as importance as migratory corridors, enacting large-scale conservation measures would address important conservation considerations for both connectivity and endemism. Enacting such large-scale conservation measures would not only elevate the Salas y Gómez and Nazca ridges as an exemplary case study, providing lessons for other marine regions seeking to implement similar measures, but could also help raise awareness on the severity of externally originating threats like climate change and plastic pollution to global audiences.

Penguins and Seals Transport Limiting Nutrients Between Offshore Pelagic and Coastal Regions of Antarctica Under Changing Sea Ice - Stephen R. Wing; Lucy C. Wing; Sorrel A. O’Connell-Milne; David Barr; Dale Stokes; Sal Genovese; James J. Leichter (Ecosystems, 2021)

Recent progress on combining geomorphological and geochronological data with ice sheet modelling, demonstrated using the last British–Irish Ice Sheet - Jeremy C. Ely; Chris D. Clark; Richard C. A. Hindmarsh; Anna L. C. Hughes; Sarah L. Greenwood; Sarah L. Bradley; Edward Gasson; Lauren Gregoire; Niall Gandy; Chris R. Stokes; David Small (Journal of Quaternary Science, 2021)
Palaeo‐ice sheets are important analogues for understanding contemporary ice sheets, offering a record of ice sheet behaviour that spans millennia. There are two main approaches to reconstructing palaeo‐ice sheets. Empirical reconstructions use the available glacial geological and chronological evidence to estimate ice sheet extent and dynamics but lack direct consideration of ice physics. In contrast, numerically modelled simulations implement ice physics, but often lack direct quantitative comparison with empirical evidence. Despite being long identified as a fruitful scientific endeavour, few ice sheet reconstructions attempt to reconcile the empirical and model‐based approaches. To achieve this goal, model‐data comparison procedures are required. Here, we compare three numerically modelled simulations of the former British–Irish Ice Sheet with the following lines of evidence: (a) position and shape of former margin positions, recorded by moraines; (b) former ice‐flow direction and flow‐switching, recorded by flowsets of subglacial bedforms; and (c) the timing of ice‐free conditions, recorded by geochronological data. These model–data comparisons provide a useful framework for quantifying the degree of fit between numerical model simulations and empirical constraints. Such tools are vital for reconciling numerical modelling and empirical evidence, the combination of which will lead to more robust palaeo‐ice sheet reconstructions with greater explicative and ultimately predictive power.

Implementation of a Data Management Quality Management Framework at the Marine Institute, Ireland - Adam Leadbetter; Ramona Carr; Sarah Flynn; Will Meaney; Siobhan Moran; Yvonne Bogan; Laura Brophy; Kieran Lyons; David Stokes; Rob Thomas (Earth Science Informatics, 2020)
The International Oceanographic Data and Information Exchange of UNESCO’s Intergovernmental Oceanographic Commission (IOC-IODE) released a quality management framework for its National Oceanographic Data Centre (NODC) network in 2013. This document is intended, amongst other goals, to provide a means of assistance for NODCs to establish organisational data management quality management systems. The IOC-IODE’s framework also promotes the accreditation of NODCs which have implemented a Data Management Quality Management Framework adhering to the guidelines laid out in the IOC-IODE’s framework. In its submission for IOCE-IODE accreditation, Ireland’s National Marine Data Centre (hosted by the Marine Institute) included a Data Management Quality Management model; a manual detailing this model and how it is implemented across the scientific and environmental data producing areas of the Marine Institute; and, at a more practical level, an implementation pack consisting of a number of templates to assist in the compilation of the documentation required by the model and the manual.

Why conserving species in the wild still matters - David L. Stokes (Biodiversity and Conservation, 2018)

Dynamics of former ice lobes of the southernmost Patagonian Ice Sheet based on a glacial landsystems approach - Christopher M. Darvill; Chris R. Stokes; Michael J. Bentley; David J. A. Evans; Harold Lovell (Journal of Quaternary Science, 2017)
Reconstructions of former ice masses from glacial geomorphology help to constrain the nature and timing of glaciation in relation to climatic forcing. This paper presents a new reconstruction of the glacial history of five ice lobes in southernmost South America: the Bahía Inútil − San Sebastián, Magellan, Otway, Skyring and Río Gallegos ice lobes. We use previous geomorphological mapping of glacial landforms to reconstruct former glacial limits and proglacial lakes, demarcate flow‐sets from the distribution of glacial lineations, and evaluate glacial landsystem signatures and their palaeoglaciological implications. Evidence suggests that the ice lobes predominantly reflect active temperate glacial landsystems, which may have switched to polythermal systems when periods of cold‐based ice developed ephemerally. This complex landsystem signature implies that the ice lobes were sensitive to regional climate variability, with active re‐advances during overall retreat of the ice margins. There is also evidence for periods of fast ice flow and possible surge‐like activity in the region, followed by the rapid retreat or even collapse of some of the ice lobes in association with proglacial lakes. Constraining our new reconstruction with published chronological information suggests that at least some of the ice lobes advanced before the global Last Glacial Maximum (gLGM: ca. 26.5–19 ka) during the last glacial cycle. Our new reconstruction demonstrates a more complex picture of ice dynamics than has previously been portrayed, and one in which the advance and retreat of the ice lobes was likely to have been primarily driven by changes in climate. As such, ice advances before the gLGM in the southernmost part of the Patagonian Ice Sheet are likely to indicate a wider climatic forcing at this time.

Landscape evolution and engineering geology: results from IAEG Commission 22 - James S. Griffiths; Martin Stokes; Doug Stead; David Giles (Bulletin of Engineering Geology and the Environment, 2012)

Local Land‐Use Planning to Conserve Biodiversity: Planners’ Perspectives on What Works - DAVID L. STOKES; MARIAN F. HANSON; DEBORAH D. OAKS; JAIME E. STRAUB; AILEEN V. PONIO (Conservation Biology, 2010)
Because habitat loss due to urbanization is a primary threat to biodiversity, and land‐use decisions in urbanizing areas are mainly made at the local level, land‐use planning by municipal planning departments has a potentially important—but largely unrealized—role in conserving biodiversity. To understand planners’ perspectives on the factors that facilitate and impede biodiversity conservation in local planning, we interviewed directors of 17 municipal planning departments in the greater Seattle (Washington, U.S.A.) area and compared responses of planners from similar‐sized jurisdictions that were “high” and “low performing” with respect to incorporation of biodiversity conservation in local planning. Planners from low‐performing jurisdictions regarded mandates from higher governmental levels as the primary drivers of biodiversity conservation, whereas those from high‐performing jurisdictions regarded community values as the main drivers, although they also indicated that mandates were important. Biodiversity conservation was associated with presence of local conservation flagship elements (e.g., salmonids) and human‐centered benefits of biodiversity conservation (e.g., quality of life). Planners from high‐ and low‐performing jurisdictions favored different planning mechanisms for biodiversity conservation, perhaps reflecting differences in funding and staffing. High performers reported more collaborations with other entities on biodiversity issues. Planners’ comments indicated that the term biodiversity may be problematic in the context of local planning. The action most planners recommended to increase biodiversity conservation in local planning was public education. These results suggest that to advance biodiversity conservation in local land‐use planning, conservation biologists should investigate and educate the public about local conservation flagships and human benefits of local biodiversity, work to raise ecological literacy and explain biodiversity more effectively to the public, and promote collaboration on biodiversity conservation among jurisdictions and inclusion of biodiversity specialists in planning departments.

Biodiversity Conservation in Local Planning - JAMES R. MILLER; MARTHA GROOM; GEORGE R. HESS; TODDI STEELMAN; DAVID L. STOKES; JAN THOMPSON; TROY BOWMAN; LAURA FRICKE; BRANDON KING; RYAN MARQUARDT (Conservation Biology, 2009)
Local land‐use policy is increasingly being recognized as fundamental to biodiversity conservation in the United States. Many planners and conservation scientists have called for broader use of planning and regulatory tools to support the conservation of biodiversity at local scales. Yet little is known about the pervasiveness of these practices. We conducted an on‐line survey of county, municipal, and tribal planning directors (n = 116 ) in 3 geographic regions of the United States: metropolitan Seattle, Washington; metropolitan Des Moines, Iowa; and the Research Triangle, North Carolina. Our objectives were to gauge the extent to which local planning departments address biodiversity conservation and to identify factors that facilitate or hinder conservation actions in local planning. We found that biodiversity conservation was seldom a major consideration in these departments. Staff time was mainly devoted to development mandates and little time was spent on biodiversity conservation. Regulations requiring conservation actions that might benefit biodiversity were uncommon, with the exception of rules governing water quality in all 3 regions and the protection of threatened and endangered species in the Seattle region. Planning tools that could enhance habitat conservation were used infrequently. Collaboration across jurisdictions was widespread, but rarely focused on conservation. Departments with a conservation specialist on staff tended to be associated with higher levels of conservation actions. Jurisdictions in the Seattle region also reported higher levels of conservation action, largely driven by state and federal mandates. Increased funding was most frequently cited as a factor that would facilitate greater consideration of biodiversity in local planning. There are numerous opportunities for conservation biologists to play a role in improving conservation planning at local scales.

Evaluating the utility of Arabidopsis thaliana as a model for understanding heterosis in hybrid crops - David Stokes; Colin Morgan; Carmel O’Neill; Ian Bancroft (Euphytica, 2007)

Developing Inflorescences of Male and Female Rumex acetosa L. Show Differences in Gibberellin Content - Tania S. Stokes; Stephen J. Croker; David E. Hanke (Journal of Plant Growth Regulation, 2003)